SISTEM PEMETAAN PEMASANGAN PAPAN IKLAN DAN VIDEOTRON DAERAH KISARAN BERBASIS WEBGIS DENGAN METODE LOCATION BASED SERVICE - Syahdan; Adi Prijuna Lubis; Andri Nata (LPPM Universitas Abdurrab, 2026)
The billboard and videotron installation service system in Kisaran is designed to utilize Location-Based Service (LBS) technology integrated with WebGIS to improve marketing effectiveness. This research was conducted through several stages, including problem identification, data collection of billboard locations from the Department of Public Works, system design using UML, system development with PHP and MySQL, and Google Maps API integration for real-time location mapping. The Haversine algorithm was applied to calculate the distance between points, while system testing was performed on coordinate accuracy and response time. The results show a coordinate accuracy of 95.6% with an average position error of ±12 meters and an average response time of 1.8 seconds. The proposed system not only maps billboard locations but also integrates services such as tenant validation, booking, and payment. Compared to previous studies, this system demonstrates advantages in integrating LBS with advertising business services. Its implementation is expected to support local governments and advertising managers in planning more effective and efficient promotional strategies.